Not without madness : perspectives on opera - Della Seta, Fabrizio (University of Chicago Press, 2012)
Opera often seems to arouse either irrational enthusiasm or visceral dislike. Such madness, as Goethe wrote, is indispensable in all theater, and yet in practice, sentiment and passion must be balanced by sense and reason. Exploring this tension between madness and reason, Not without Madness presents new analytical approaches to thinking about eighteenth- and nineteenth-century opera through the lenses of its historical and cultural contexts. In these twelve essays, Fabrizio Della Seta explores the concept of opera as a dramatic event and an essential moment in the history of theater. Examini.